Menilik Tradisi Suroan pada Masyarakat Jawa di Kelurahan Cahaya Mas - Febriyanto, Dedi; Muslimin, Muslimin; Karimah, Latifatul (YASIN, 2023)
Suroan is one of the typical traditions of Javanese society. These traditions contain various deep meanings and noble values. This study aims to reveal the meaning and value of the suroan tradition in Javanese society in Cahaya Mas Village. The research was conducted using qualitative methods. Data were collected through observation, interviews, and documentation. Data analysis was carried out descriptively by outlining the meanings and values contained in the suroan tradition in the Javanese community in Cahaya Mas village. The results showed that the suroan tradition in the life of the Javanese community, especially in the Cahaya Mas village was carried out as a form of hope, gratitude to God, and at the same time opening virtues in the new year in order to obtain a life filled with blessings. In practice, this goal is symbolized in various components of typical food, such as jenang sengkolo, jenang abang white jenang, golong limo, sego brok, sacred sekol, wulam sari. This component is a symbol of hope for the Javanese people in welcoming the new year. The suroan tradition carried out also contains noble values which include cultural values, cooperation values, responsibility values, social care values, tolerance values, and religiosity values. These values are very feasible to be instilled and practiced in the life of society, nation and state.